Towards low-carbon heavy oil recovery: multi-source renewable energy integration and multi-objective optimization - Qi Liu; Hongjuan Hou; Yaochen Wang; Min Deng; Tianshu Li; Yan Jia; Eric Hu (Fuel, 2026)

Disruption in absorption and metabolism of folate mediates DNA damage activated germline apoptosis in 6-PPD quinone exposed Caenorhabditis elegans - Yuxing Wang; Tianshu Wu; Dayong Wang (Environmental Pollution, 2026)

Corrigendum to “A rapid method to generate an all-female population in common carp (Cyprinus carpio) using the neomale carp of F0 population with targeted aromatase mutations” Aquaculture, Volume 612, Part 1, 15 January 2026, 743185 - Yuting Xie; Hongfei Bao; Guanghui Chen; Xuehui Li; Yonglin Ruan; Qiyong Lou; Xia Jin; Jiangyan He; Tianshu Zhang; Jian Wang; Xueqiao Qian; Gang Zhai; et al. (Aquaculture, 2026)

Functional characterization of AoPLL16 in salt tolerance regulated by AobHLH31 in Aquilegia oxysepala - Xuanyu Shen; Haihang Yu; Zhijia Chen; Shunyuan Yang; Tianshu Wang; Ying Qian; Yuan Meng; Yun Bai (Plant Science, 2026)

Collision-free path planning for underwater gliders in time-varying currents via dual-archive niching differential evolution - Zezhong Li; Rongshun Juan; Yang Li; Shoufu Liu; Tianshu Wang; Shuaikun Shi; Leihao Du; Wanjun Feng; Zhongke Gao (Ocean Engineering, 2026)

Mechanism of rice protein amyloid fibrils-induced structural changes of soybean protein during high-moisture extrusion: Focusing on multi-scale structural evolution - Jinming Ma; Kaizhi Li; Deyin Pan; Peng Wang; Mohamed E. Hassan; Wenyi Yang; Tianshu Zhang; Xiaoshuai Yu; Baoxin Lu; Zhigang Xiao (Food Research International, 2026)

Diverse crop rotation promoted crop yield via microbial networks in North China Plain - Shuting Yu; Yubin Zhao; Tianshu Wang; Shuihong Yao; Yang Gao; Jun Li; Xinhua Peng; Bin Zhang (European Journal of Agronomy, 2026)

A two-dimensional nanocatalytic engineered saliva immunosensor for acute myocardial infarction high-sensitivity detection - Jingyi Yang; Lei Li; Xuanyu Xiao; Yuting Zhong; Zetai Zheng; Yue Zhou; Tianshu Wang; Chenxu Wang; Wei Deng; Chenjun Xu; Chen Li; Qinsheng Hu; et al. (Chemical Engineering Journal, 2026)

How additives steer sewage sludge hydrochar properties: Divergent pathways of MgO/CaO versus sawdust in carbon/nutrient fate and magnetism - Chen Zhang; Guo Chen; Qinghai Wang; Huafen Li; Yanan Wan; Guoxin Sun; Ke Wang; Tianshu Chu; Ruilun Zheng (Bioresource Technology, 2026)

Retraction notice to “Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China” [Sci. Total Environ. 898 (2023) 165303] - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2026)

P-NISPH: A Potential Combined Non-inertial Smoothed Particle Hydrodynamics Method for Large-amplitude Liquid Sloshing in Microgravity Environments - Jiawei Huo; Tianshu Wang; Xibin Cao (Advances in Space Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Source, transport and impact of biomass burning emissions in spring 2024 in Yunnan, China - Lihui Lv; Feng Xiang; Haitao Xie; Fei Qiu; Ying Pan; Zihuai Yi; Zenan Wang; Zhichao Liu; Limei Bi; Lu Zhao; Qianqian Sun; Shuai Wang; et al. (Journal of Environmental Sciences, 2026)

Experimental Investigation into the Effect of Process Parameters on Borehole Formation in Bedded Shale by Swirling Abrasive Water Jet - Kang Cheng; Zhongwei Huang; Jingru Hu; Jingbin Li; Bing Xi; Tianshu Wang; Huan Li; Gensheng Li (Rock Mechanics and Rock Engineering, 2026)

Curculigoside Alleviates CSDS-induced Depressive-like Behavior by Modulating Pyramidal Neuron Excitability and Synaptic Transmission - Yuhong Jing; Tianshu Zhang; Zihao Wei; Huaiyuan Wang; Tianqi Gao; Yanling Liu; Lin Cong; Lianbin Zhao; Shuoxin Xie; Lu Liu; Xinmeng Zhang; Tongrui Wu; et al. (NeuroMolecular Medicine, 2026)

Ammonium may emerge as the primary driver of future aerosol acidity, replacing the historical role of sulfate over the coastal area of North China: Insights from a megacity (Qingdao) - Wenshuai Li; Yaoyu Song; Tianshu Chen; Yuxuan Qi; Guanru Wu; Xinshuo Wang; Wenwen Xie; Lifang Sheng; Wencai Wang; Wenjun Qu; Yang Zhou (Atmospheric Environment, 2026)

Toward sustainable lithium recovery from brine: a hydrothermal carbon-coating strategy for minimizing Mn dissolution in ion-sieve adsorbents - Tianshu Bao; Congcong Li; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Lili Yu; Xinjuan Hou; Aiping Peng; Ming Ye (Resources, Conservation and Recycling, 2026)

Winter fallow straw–nitrogen co-application enhances rice yield and stability by regulating soil organic matter physical fractions and chemical composition - Xi Chen; Danni Li; Min Peng; Yueling Zhang; Tianshu Wang; Jingdong Mao; Shuihong Yao; Bin Zhang (Agriculture, Ecosystems & Environment, 2026)

Study on the erosion mechanism of calcium-based sand erosion-resistant materials in an ion-stress coupled environment - Tianshu Wang; Peng Li; Feiyu Yang; Kai Yi (Marine Georesources & Geotechnology, 2026)

Corrigendum to “maternal smoking during pregnancy could accelerate biological aging in the adulthood: Evidence from a perspective study in UK biobank.” [Sci. Total Environ., 951(2014) 175150] - Wenbo Jiang; Xinyi Sun; Conghui Qiao; Xinyu Shan; Yiwei Tang; Yingdong Zuo; Xinyang Wang; Tianshu Han; Wei Wei (Science of The Total Environment, 2026)

Reinforcement learning-based path planning for underwater gliders using ocean current forecasts - Yatao Zhou; Yang Li; Rongshun Juan; Tianshu Wang; Zezhong Li; Shoufu Liu; Wei Ma; Zhongke Gao (Ocean Engineering, 2026)

Revealing ozone persistence under typhoon subsidence in the Greater Bay Area using lidar observations - Rui He; Zhongcai Wang; Yongfan Wu; Yan You; Yan Xiang; Andi Zhang; Chenglei Pei; Tianshu Zhang (Atmospheric Research, 2026)

Generation of an infectious cDNA clone of BJ-Swzp-2022, a Group III Isolate of Getah Virus - Dongni Kong; Liang Meng; Dan Liu; Jia Wang; Xiaojie Huang; Tianshu Zhai; Yong Deng; Qi Xue; Hongju Wu; Yaqing Mao; Haiwei Wang; Huawei Wu (Virus Genes, 2026)

Chrysanthemum classification method via multi-stream deep color space feature fusion - Jian Jiang; Xichen Yang; Hui Yan; Jia Liu; Yifan Chen; Zhongyuan Mao; Tianshu Wang (Computers and Electronics in Agriculture, 2026)

Enhanced caproic acid production through electro-fermentation: A novel approach for resource utilization of lignocellulosic waste - Tianshu Liu; Jianzheng Li; Furao Wang; Jia Meng (Environmental Research, 2026)

Toward smart aquaculture: A review of multimodal methods, datasets, and applications from the modality perspective - Qinyue Zhang; Shasha Wang; Tianshu Zhang; Guiming Ren; Lingling Zhang; Yangfan Wang; Bing Zheng; Juan Li; Haiyong Zheng (Computers and Electronics in Agriculture, 2026)

A rapid method to generate an all-female population in common carp (Cyprinus carpio) using the neomale carp of F0 population with targeted aromatase mutations - Yuting Xie; Hongfei Bao; Guanghui Chen; Xuehui Li; Yonglin Ruan; Qiyong Lou; Xia Jin; Jiangyan He; Tianshu Zhang; Jian Wang; Xueqiao Qian; Gang Zhai; et al. (Aquaculture, 2026)

Event-triggered model predictive control for trajectory tracking of underwater gliders in currents - Tianshu Wang; Rongshun Juan; Man Luo; Jin Chen; Yang Li; Yatao Zhou; Zhongke Gao (Ocean Engineering, 2026)

Change of chemical compositions of the regional free troposphere in North China during COVID-19: Observational evidence from the Mt. Tai observatory - Yue Sun; Yujiao Zhu; Can Dong; Yingnan Zhang; Yujian Bi; Di Wu; Xiangkun Yin; Hengqing Shen; Tianshu Chen; Hongyong Li; Yuqiang Zhang; Qinyi Li; et al. (Atmospheric Environment, 2026)

Long-range straight-line path tracking for underwater gliders using reinforcement learning and ocean current forecasts - Yatao Zhou; Rongshun Juan; Yang Li; Tianshu Wang; Wei Guo; Ming Yang; Zhongke Gao (Ocean Engineering, 2025)

Understanding clouds and precipitation over the Mount Qomolangma: how does the aerosol activation effect exist? - Xiangde Xu; Wenyue Cai; Tianliang Zhao; Hua Zhang; Xueliang Guo; Wenqing Liu; Tianshu Zhang; Runze Zhao; Chong Wu; Yueqing Li; Lei Wang; Peng Yan; et al. (Science Bulletin, 2025)

Fixed-time backstepping control of attitude tracking in 3D space for an autonomous underwater glider - Man Luo; Tianshu Wang; Rongshun Juan; Shoufu Liu; Junhe Wan; Zhongke Gao (Ocean Engineering, 2025)

Is destabilized coupled flat plate membrane technology valuable for high-salinity mine water treatment? - Liyao Wang; Xianfeng Tan; Jianguo Fan; Hongnian Chen; Tianshu Xu; Mengqing Li; Jinglan Hong (Environmental Research, 2025)

Naringenin targets and inhibits Monoamine Oxidase A/B to bidirectionally regulate intestinal motility. - Qi Li; Yi Chen; Yige Zhang; Canwei Xu; Ting Tang; Yunzhi Qian; Ong Shun seng; Yujuan Wang; Ling Fang; Tianshu Xu (Chemico-Biological Interactions, 2025)

Underestimated inhibition of cloud water by dust aerosols in the Yangtze River Delta - Tianshu Xu; Yinshan Yang; Chuanfeng Zhao; Qiao Wang; Kun Jia; Yuying Wang; Yahui Tang; Xing Yan (Atmospheric Environment, 2025)

Study on the propagation processes and driving mechanisms of meteorological, hydrological, and agricultural droughts on the Mongolian Plateau - Li Mei; Han Aru; Siqin Tong; Yongfang Wang; Enliang Guo; Tianshu Zhang; Shan Yin; Yuhai Bao (Journal of Hydrology, 2025)

Nicotinamide metabolic dysregulation plays a key role in Benzo[a]pyrene-induced adverse birth outcomes: Evidence from multi-omics profiling, experimental and epidemiological validation - Nan Zhao; Wei Song; Tianshu Sun; Weiwei Wu; Yongliang Feng; Ning Ma; Suping Wang (Journal of Hazardous Materials, 2025)

Enhancing transparency in land use change modeling: Leveraging eXplainable AI techniques for urban growth prediction with spatially distributed insights - Zelin Wang; Tianshu Feng; Abolfazl Safikhani; Emre Tepe (Computers, Environment and Urban Systems, 2025)

Vertical distribution and regional transport of air pollution over Northeast China: Insights from an intensive aircraft study - Ye Shan; Yujiao Zhu; Haoxin Sui; Na Zhao; Hongyong Li; Liang Wen; Tianshu Chen; Yanbin Qi; Wenlong Qi; Xinfeng Wang; Yuqiang Zhang; Likun Xue; et al. (Atmospheric Environment, 2025)

Breeding for yield improvements increases soybean seed N uptake due to enhanced N fixation under soil compaction - Tianshu Wang; Li Wang; Huajun Sun; Shuihong Yao; Yili Meng; Dawei Guan; Xinhua Peng; Bin Zhang (Plant and Soil, 2025)

Corrigendum to ‘Joint utilization of Chinese milk vetch and lime materials mitigates soil cadmium risk and improves soil health in a double-cropping rice system’ [Chemosphere 363 (2024) 142784] - Yikun Wang; Kai Wang; Tianshu Wang; Ting Liang; Jia Liu; Xiaofen Chen; Changxu Xu; Weidong Cao; Hongli Fan (Chemosphere, 2025)

Amplified urban heat island effect in southern china’s old towns following atmospheric regulation policies - Junxiao Zou; Hans W. Chen; Haodong Li; Qiao Wang; Guoqiang Wang; Kun Jia; Ziyue Chen; Chuanfeng Zhao; Wenzhong Shi; Yinshan Yang; Yahui Tang; Jiayi Chen; et al. (Sustainable Cities and Society, 2025)

Mushroom residue extract-based media enhanced the enrichment and isolation of cellulose-degrading bacteria - Xiaoli Luo; Tianshu Wang; Yili Meng; Li Li; Shuihong Yao; Huawei Wu; Jun Li (Bioresource Technology Reports, 2025)

A visual balance calculation method for wemaps combining fuzzy clustering and multi-factor driving - Rongjuan Ma; Haowen Yan; Xiaomin Lu; Zhaoyang Hou; Xiaolong Wang; Pengbo Li; Tianshu Chu; Fukang Mao (Earth Science Informatics, 2025)

Evaluating foraminifera-bound δ15N as an ocean deoxygenation proxy: the influence of oxygen-deficient zone depths - Tianshu Kong; Thomas Lee; Kameko Landry; Ruixiang Zhai; Sijia Dong; Xingchen Tony Wang (Frontiers in Marine Science, 2025)
The nitrogen isotopic composition of shell-bound organic matter in planktonic foraminifera (FB-δ 15 N) is widely used as a proxy for past ocean deoxygenation because water-column denitrification in oxygen-deficient zones (ODZs; [O 2 ] < 5 µmol/kg) preferentially removes 14 N, enriching the remaining nitrate in 15 N. Typically, increases in FB-δ 15 N records from ODZ-influenced regions are interpreted as evidence of ODZ expansion or intensification. However, planktonic foraminifera predominantly feed on organic nitrogen derived from the subsurface nitrate immediately below the euphotic zone, often above ODZ core depths. It remains unclear if the δ 15 N maxima observed within ODZ cores, reflecting denitrification intensity at a given location, directly correlates with the FB-δ 15 N values recorded above. Here, we combine new and published data from the eastern tropical Pacific ODZs to examine relationships among subsurface nitrate δ 15 N, ODZ δ 15 N maxima, and ODZ upper-boundary depths. Our analysis reveals a strong correlation between subsurface nitrate δ 15 N and ODZ δ 15 N maxima (R 2 = 0.56-0.79), supporting the use of FB-δ 15 N as an indicator of denitrification intensity within ODZ regions. However, subsurface nitrate δ 15 N also correlates strongly with the ODZ upper-boundary depth (R 2 = 0.57-0.59), with lower δ 15 N values observed where ODZs are deeper. For example, at our new study sites in the Eastern Tropical North Pacific (5 – 8°N), where the ODZ upper-boundary depth is ~300 m, the δ 15 N maxima (>10‰) at the ODZ core decrease upward to subsurface nitrate δ 15 N values of ~6.5‰ — only slightly higher than the global pycnocline nitrate δ 15 N. These results suggest that variations in ODZ depth should be accounted for when interpreting FB-δ 15 N records (and other δ 15 N archives) from ODZ regions. Under warmer conditions, organic matter remineralization may become shallower due to the temperature dependence of respiration, shifting ODZs upward and elevating FB-δ 15 N even without changes in denitrification rates. To more robustly reconstruct ODZ history using FB-δ 15 N, we recommend using multiple sites from the ODZ interior to regions beyond their modern boundaries. Cores situated outside modern ODZs, where thermocline nitrate δ¹ 5 N still carries the ODZ signature, are ideal for tracing ODZ expansions and contractions, while cores from within the modern ODZs provide complementary constraints on ODZ intensity and vertical structure.

Giant lacustrine bioherms in the northeastern Qinghai-Tibet Plateau (western Qaidam Basin) during the Early–Middle Miocene: Carbonate fabrics, growth patterns, and environmental significance - Hui Xie; Fei Li; Xiang Li; Jiangong Wang; Chaojin Lu; Yuefeng Shen; Yalan Li; Zengjun Wang; Tianshu Zhang; Yangfan Li; Tao Wu; Ying Li (Sedimentary Geology, 2025)

Comparison of the polluted dust plume and natural dust air mass in a spring dust event in Beijing 2023 - Zhenyi Chen; Zhonghao Zhou; Chengli Ji; Zhiliang Yao; Jiajia Mao; Zhicheng Wang; Yan Xiang; Tianshu Zhang; Yi Zhou; Zijian Chen; Gang Dou (Journal of Environmental Sciences, 2025)

Adjustable Brønsted type ionic liquid catalyst based on porous cellulose microspheres for green and efficient catalytic system in transesterification - Tao Wang; Xiqing Wang; Tianshu Liu; Yujie Fu (Fuel, 2025)

Machine Learning-Based Study of Wire Icing Growth under Coexisting Freezing Rain and Supercooled Fog - Haopeng Wu; Shengjie Niu; Seong Soo Yum; Jingjing Lyu; Siting Wang; Pyosuk Seo; Yixiao He; Tianshu Wang; Xinyi Wang (Journal of Meteorological Research, 2025)

Multi-tissue Methylation Analysis of Alzheimer’s Disease: Insights into Pathways, Modules, and Key Genes - Tianshu Zhu; Yue Wang; Han Wang; Zheyu Xu; Peng-Fei Zhang; Zhiming Lu (Journal of Molecular Neuroscience, 2025)

Long-term properties of grout-soil composite eroded by seawater environment in submarine tunnel - Chengqian Wang; Peng Li; QingSong Zhang; Tianshu Wang (Tunnelling and Underground Space Technology, 2025)

Insight into ion-induced stability degradation in all-perovskite tandem photovoltaics: quantitative characterization and effective manipulation strategies - Yining Bao; Tianshu Ma; Yuqi Zhang; Luolei Shi; Linling Qin; Changlei Wang; Guoyang Cao; Xiaofeng Li; Zhenhai Yang (Science Bulletin, 2025)

Increased VOC reactivity forcing ozone pollution in the Yangtze River Delta region, China: Evidence from an eight-year observation at an urban site and implications for future control strategies - Xin Zhang; Miao Ning; Wanghui Chu; Yuanzhou Dong; Xurong Shi; Tianshu Chen; Qiang Ma; Lijuan Wang; Yezheng Wu; Wei Zheng; Zhijun Wu (Journal of Hazardous Materials, 2025)

Design of four-level phase-change memory Ge2Sb2Te5/Ge50Te50 bilayer films and study of their crystallization behaviors - Ling Liu; Han Gu; Qiyu Cai; Liqi Zhu; Jie Song; Weihua Wu; Zixin Wang; Tianshu Lai (Chemical Engineering Journal, 2025)

Tracing carbon-water pressures in the Belt and Road Initiative region from a "historical-future" perspective - Ziheng Li; Yijie Zhai; Tianzuo Zhang; Shuo Wang; Kang Wang; Changting Li; Tianshu Xu; Jinglan Hong (Resources, Conservation and Recycling, 2025)

Design, synthesis, and application of negative ion-ion sieve synergistic adsorbent based on cross-linked carrier - Tianshu Bao; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Yong Wang; Xinjuan Hou; Aiping Peng; Ming Ye (Desalination, 2025)

A new amine isolated from Urtica thunbergiana Siebold & Zucc - Mencuo La; Qiqi Wang; Yao Wang; Ruisha Mian; Tianshu Zhao; Fangfang He; Chengbiao Chen; Denglang Zou (Natural Product Research, 2025)

Shipborne lidar measurements of ozone over the southeastern coastal regions of China in winter - Lihui Lv; Yan Xiang; Jie Wang; Ying Pan; Zenan Wang; Zihuai Yi; Tianshu Zhang; Wenqing Liu (Environmental Research, 2025)

Study on the characteristics of precipitation particle size distribution during freezing weather in the southwest mountainous areas of China - Haopeng Wu; Shengjie Niu; Seong Soo Yum; Jingjing Lü; Chunsong Lu; Yue Zhou; Jing Sun; Yixiao He; Tianshu Wang; Xinyi Wang (Science China Earth Sciences, 2025)

Carbonaceous cores serve as surrogates for environmental particulate matter inducing vascular endothelial inflammation via inflammasome activation - Yán Wāng; Chunzhi Wang; Yang Jiang; Tian Wang; Tianshu Wu; Meng Tang (Journal of Hazardous Materials, 2025)

Insights into the environmental–economic sustainability of rice production in China - Liyao Wang; Tianzuo Zhang; Xinying Zhou; Tianshu Xu; Changting Li; Ziheng Li; Shuo Wang; Mengqing Li; Jinglan Hong (Journal of Cleaner Production, 2025)

Experimental research of heating characteristics on an air source heat pump system with capillary direct floor radiant - Jianhui Niu; Haichao Wang; Tianshu Lv; Shuxue Xu (International Journal of Refrigeration, 2025)

Correction: Quantitative Analysis of Physical Stability Mechanisms of Amorphous Solid Dispersions by Molecular Dynamic Simulation - Hao Zhong; Tianshu Lu; Ruifeng Wang; Defang Ouyang (The AAPS Journal, 2025)

Variation of biogenic VOC contribution to ozone formation with reduced anthropogenic precursor emissions: Coupling online observation and future scenario simulation - Yuhong Liu; Tianshu Chen; Zhaokun Ma; Qinyi Li; Yang Gao; Likun Xue; Wenxing Wang (Science of The Total Environment, 2025)

Quantitative Analysis of Physical Stability Mechanisms of Amorphous Solid Dispersions by Molecular Dynamic Simulation - Hao Zhong; Tianshu Lu; Ruifeng Wang; Defang Ouyang (The AAPS Journal, 2024)

Incentivizing emission controls toward clean air and carbon neutrality in China: Perspectives from a risk-based approach for air quality management - Kimberly Tasha Jiayi Tang; Changqing Lin; Zhe Wang; Tianshu Zhang; Lu Li; Tze Wai Wong; Cui Guo (Science of The Total Environment, 2024)

The interaction between plasma polymetals and lifestyle on cognitive dysfunction in occupational aluminum exposed workers: A cross-sectional study in China - Tianshu Wang; Lingshan Xue; Chenyang Li; Dan Zhao; Jiaping Huan; Xiao Han; Jing Song; Linping Wang; Huifang Zhang; Qiao Niu; Baolong Pan; Jinzhu Yin; et al. (NeuroToxicology, 2024)

Similarity of Chinese and Pakistani oral microbiome - Xiaofang Sun; Binghua Han; Qian Han; Qiaoling Yu; Sijie Wang; Jie Feng; Tianshu Feng; Xiaoshan Li; Shiheng Zhang; Huan Li (Antonie van Leeuwenhoek, 2024)

Internally-cooled atmospheric water harvesting enabling improved productivity - Yaohui Feng; Lurong Ge; Qian Li; Ruzhu Wang; Tianshu Ge (Water Research, 2024)

Milk vetch returning combined with lime materials alleviates soil cadmium contamination and improves rice quality in soil-rice system - Yikun Wang; Kai Wang; Ting Liang; Tianshu Wang; Jia Liu; Xiaofen Chen; Changxu Xu; Weidong Cao; Hongli Fan (Science of The Total Environment, 2024)

Maternal smoking during pregnancy could accelerate aging in the adulthood: evidence from a perspective study in UK Biobank - Wenbo Jiang; Qianqian Lei; Wei Gao; Xinyi Sun; Conghui Qiao; Xinyu Shan; Yiwei Tang; Yingdong Zuo; Xinyang Wang; Tianshu Han; Wei Wei; Dandan Zhang (Science of The Total Environment, 2024)

A convolutional neural networks method for tropospheric ozone vertical distribution retrieval from Multi-AXis Differential Optical Absorption Spectroscopy measurements - Zijie Wang; Xin Tian; Pinhua Xie; Jin Xu; Jiangyi Zheng; Yifeng Pan; Tianshu Zhang; Guangqiang Fan (Science of The Total Environment, 2024)

The influence of mudstone lithofacies sedimentation on the development of shale oil “sweet-spot intervals” within large down-warped lacustrine basins in China - Youliang Feng; Zhi Yang; Wenqi Jiang; Hong Zhang; Tianshu Zhang; Chang Liu; Pan Li; Jichang Zhu; Xiaoni Wang (Marine and Petroleum Geology, 2024)

Prenatal prednisone exposure disturbs fetal kidney development and its characteristics - Zhiping Xia; Songdi Wang; Wen Wang; Yutang Liu; Tianshu Yang; Hui Wang; Ying Ao (Journal of Environmental Sciences, 2024)

Sustainability assessment for China's intensive dairy farming: Integrating environmental and economic perspectives - Tianshu Xu; Tianzuo Zhang; Ziyue Cheng; Ziheng Li; Shuo Wang; Xinying Zhou; Changting Li; Liyao Wang; Mengqing Li; Jinglan Hong (Sustainable Production and Consumption, 2024)

High-precision motion control of underwater gliders based on reinforcement learning - Rongshun Juan; Tianshu Wang; Shoufu Liu; Yatao Zhou; Wei Ma; Wendong Niu; Zhongke Gao (Ocean Engineering, 2024)

Sensitivity of cloud microphysics to aerosol is highly associated with cloud water content: Implications for indirect radiative forcing - Yuan Wang; Hailing Jia; Ping Zhang; Fang Fang; Jiayi Li; Lei Zhu; Yang Wang; Tianshu Wang; Jiming Li (Atmospheric Research, 2024)

m6A methylation in myocardial tissue of septic mice analyzed using MeRIP/m6A-sequencing and RNA-sequencing - Xue Liang; Xiaotong Hu; Jiao Li; Boyang Zhang; Tianshu Gu; Hualing Wang; Mingzhong Zhang; Xiaodong Xia; Siyu Guan; Wenfeng Shangguan; Shuai Miao; Weiding Wang; et al. (Functional & Integrative Genomics, 2024)

Research on low-power driving fatigue monitoring method based on spiking neural network - Tianshu Gu; Wanchao Yao; Fuwang Wang; Rongrong Fu (Experimental Brain Research, 2024)

Joint utilization of Chinese milk vetch and lime materials mitigates soil cadmium risk and improves soil health in a double-cropping rice system - Yikun Wang; Kai Wang; Tianshu Wang; Ting Liang; Jia Liu; Xiaofen Chen; Changxu Xu; Weidong Cao; Hongli Fan (Chemosphere, 2024)

Heatwave exacerbates air pollution in China through intertwined climate-energy-environment interactions - Tianshu Chen; Tao Wang; Likun Xue; Guy Brasseur (Science Bulletin, 2024)

A Perspective on Evaluating Life Stage Differences in Drug Dosages for Drug Labeling and Instructions - Tianshu Gu; Guiying Wang; Edwin J. C. van den Oord; Emanuel Goldman; Chengyuan Yang; Ning Xie; Lan Yao; Cong-Yi Wang; Monica Jablonski; Kunal Ray; Fengxia Liu; Wensen Pan; et al. (The AAPS Journal, 2024)

Interference of microplastics on autotrophic microbiome in paddy soils: Shifts in carbon fixation rate, structure, abundance, co-occurrence, and assembly process - Jiaohui Fang; Zihao Sheng; Jian Liu; Changchao Li; Tianshu Lyu; Zhenyang Wang; Honghai Zhang (Journal of Hazardous Materials, 2024)

Stability and 3D-printing performance of high-internal-phase emulsions based on ultrafine soybean meal particles - Haiqiang Liao; Tianshu Jiang; Lei Chen; Guozhen Wang; Qian Shen; Xiuying Liu; Wenping Ding; Lijie Zhu (Food Chemistry, 2024)

Transformation mechanisms of antidepressants in biological wastewater treatment: Removal kinetic, transformation products and pathways - Gang Wu; Ruijing Yao; Yi Zhang; Ming Ying; Tianshu Wu; Wenqi Jiang; Depeng Wang; Xu-Xiang Zhang (Chemical Engineering Journal, 2024)

Promoting sustainable potato production - Insights from an integrated life cycle environmental–economic assessment - Tianzuo Zhang; Changting Li; Shuo Wang; Ziyue Cheng; Ziheng Li; Tianshu Xu; Xinying Zhou; Wei Chen; Jinglan Hong (Agricultural Systems, 2024)

A quantitative analysis of causes for increasing ozone pollution in Shanghai during the 2022 lockdown and implications for control policy - Yingnan Zhang; Qingyan Fu; Tao Wang; Juntao Huo; Huxiong Cui; Jiangshan Mu; Yue Tan; Tianshu Chen; Hengqing Shen; Qinyi Li; Likun Xue (Atmospheric Environment, 2024)

An atmospheric water harvesting system based on the “Optimal Harvesting Window” design for worldwide water production - Qian Li; Zhao Shao; Qihong Zou; Quanwen Pan; Yao Zhao; Yaohui Feng; Wenwen Wang; Ruzhu Wang; Tianshu Ge (Science Bulletin, 2024)

Efficacy and safety of transvaginal mesh repair in a cohort with a minimum of 10-year follow-up - Zhibo Zhang; Jianbin Guo; Weijie Tian; Ye Zhang; Yuelun Zhang; Tianshu Sun; Jiali Duan; Xinmiao Bao; Yuan Wang; Yang Ye; Qianqian Gao; Honghui Shi; et al. (Science China Life Sciences, 2024)

Low-dose cadmium telluride quantum dots trigger M1 polarization in macrophages through mTOR-mediated transcription factor EB activation - Tingting Wei; Na Liu; Yongshuai Yao; Xiaoquan Huang; Zhihui Wang; Tianshu Wu; Ting Zhang; Yuying Xue; Meng Tang (NanoImpact, 2024)

Process intensification of tar chemical looping reforming based on ReaxFF reaction kinetics investigation - Zhe Li; Tianshu Wang; Yang Sun; Zhe Cui; Bin Liu; Wende Tian (Journal of Cleaner Production, 2024)

The association between blue light exposure and incidence of type 2 diabetes: A prospective study of UK biobank - Cheng Wang; Yang Zhao; Qianqi Hong; Yating Lei; Shengyuan Wang; Weiqi Wang; Wei Wei; Changhao Sun; Tianshu Han (Environmental Research, 2024)

Soil compaction development facilitated the decadal improvement of the root system architecture and rhizosheath soil traits of soybean in the North China Plain - Li Wang; Tianshu Wang; Shuihong Yao; Huajun Sun; Bin Zhang (Soil and Tillage Research, 2024)

Performance analysis of a rotary desiccant wheel using polymer material with high water uptake and low regeneration temperature - Yanan Xue; Qian Li; Ruzhu Wang; Tianshu Ge (International Journal of Refrigeration, 2024)

Vertical profiles and regional transport of ozone in typical area of Yangtze-Huaihe River Basin during the autumn base on multiple lidars - Xinqi Wang; Hong Zhang; Xingyuan Hong; Yan Xiang; Shuibing Wang; Tianshu Zhang; Zhiyong Qin; Jingping Ou (Atmospheric Pollution Research, 2024)

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)

Oropharyngeal aspirated Ag/TiO2 nanohybrids: Transformation, distribution and toxicity - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Yongshuai Yao; Zhihui Wang; Yuanyuan Hu; Qing Fang; Shujing Guan; Yuying Xue; Tianshu Wu; Ting Zhang; et al. (Science of The Total Environment, 2024)

A comprehensive insight into the transformation pathways and products of fluoxetine and venlafaxine in wastewater based on molecular networking nontarget screening - Gang Wu; Tianshu Wu; Yiran Chen; Xiwei He; Peng Liu; Depeng Wang; Jinju Geng; Xu-Xiang Zhang (Science of The Total Environment, 2024)

Research on autonomous decision-making technology for once-through steam generator - Ren Yu; Cheng Li; Wenmin Yu; Xiaosen Song; Tianshu Wang (Annals of Nuclear Energy, 2023)

Ag/TiO2 nanohybrids induce fibrosis-related epithelial-mesenchymal transition in lung epithelial cells and the influences of silver content and silver particle size - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Lingyue Zou; Changcun Bai; Yongshuai Yao; Zhihui Wang; Yuying Xue; Tianshu Wu; Ting Zhang; Meng Tang (Science of The Total Environment, 2023)

RETRACTED: Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2023)

Spartina alterniflora invasion differentially alters microbial residues and their contribution to soil organic C in coastal marsh and mangrove wetlands - Xueli Ding; Weiqi Wang; Jiahui Wen; Tianshu Feng; Josep Peñuelas; Jordi Sardans; Chao Liang; Evgenios Agathokleous; Chun Wang; Zhaoliang Song; Qiang Li; Timothy R. Filley; et al. (CATENA, 2023)

Biogenic volatile organic compounds enhance ozone production and complicate control efforts: Insights from long-term observations in Hong Kong - Yingnan Zhang; Jianing Dai; Qinyi Li; Tianshu Chen; Jiangshan Mu; Guy Brasseur; Tao Wang; Likun Xue (Atmospheric Environment, 2023)

Dynamics modeling and typical motion performance analysis for a multi-joint autonomous underwater vehicle - Kexian Liu; Tianshu Song; Xuehan Xu; Haoyu Wang; Qinghao Meng (Ocean Engineering, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

An update on the biological effects of quantum dots: From environmental fate to risk assessment based on multiple biological models - Xinyu Wang; Tianshu Wu (Science of The Total Environment, 2023)

One-step in situ construction of anisotropic bilayer hydrogel with high sensitivity and wide detection range for adaptive tactile sensing - Lujing Wang; Yangrong Peng; Jingtong Liu; Chenxin Yi; Tianhang Han; Lang Ding; Zhenyang Luo; Tianshu Sun; Shuai Zhou (Chemical Engineering Journal, 2023)

Correction to: Preparation of AuNP‑CQD/PDA/GO anode for MFC and its treatment of oily sewage from ships - Tianshu Wang; Peibo Shi; Mingyu Wang; Shaojun Zhang (Environmental Science and Pollution Research, 2023)

Preparation of AuNP-CQD/PDA/GO anode for MFC and its treatment of oily sewage from ships - Tianshu Wang; Peibo Shi; Mingyu Wang; Shaojun Zhang (Environmental Science and Pollution Research, 2023)

Two-year online measurements of volatile organic compounds (VOCs) at four sites in a Chinese city: Significant impact of petrochemical industry - Jiangshan Mu; Yingnan Zhang; Zhiyong Xia; Guolan Fan; Min Zhao; Xiaoyan Sun; Yuhong Liu; Tianshu Chen; Hengqing Shen; Zhanchao Zhang; Huaicheng Zhang; Guang Pan; et al. (Science of The Total Environment, 2023)

Changes in the m6A RNA methylome accompany the promotion of soybean root growth by rhizobia under cadmium stress - Xue Han; Jialin Wang; Yu Zhang; Youlin Kong; Huiying Dong; Xuezhen Feng; Tianshu Li; Changjun Zhou; Jidong Yu; Dawei Xin; Qingshan Chen; Zhaoming Qi (Journal of Hazardous Materials, 2023)

Advances in coastal ocean boundary layer detection technology and equipment in China - Haitao Zheng; Youwen Sun; Tao Luo; Xueling Cheng; Shiyong Shao; Shouyin Zheng; Bangyi Tao; Bin Chen; Qianguang Tu; Kan Huang; Bingbing Wang; Mian Wang; et al. (Journal of Environmental Sciences, 2023)

Forecasting and analysis of the effect of lifestyle on cognitive dysfunction induced by occupational aluminum exposure based on Bayesian networks - Dan Zhao; Xiao Han; Jiaping Huan; Dan Gao; Tianshu Wang; Jing Song; Linping Wang; Huifang Zhang; Tiane Luo; Baolong Pan; Qiao Niu; Xiaoting Lu (Environmental Toxicology and Pharmacology, 2023)

Imidazolium-based ionic liquid confined into ordered mesoporous MCM-41 for efficient dehumidification - Lurong Ge; Yaohui Feng; Yanjun Dai; Ruzhu Wang; Tianshu Ge (Chemical Engineering Journal, 2023)

What are the Lacustrine Fine-Grained Gravity Flow Sedimentation Process and the Genetic Mechanism of Sweet Sections for Shale Oil? - Caineng Zou; Youliang Feng; Zhi Yang; Wenqi Jiang; Songqi Pan; Tianshu Zhang; Xiaoni Wang; Jichang Zhu; Jiarui Li (Journal of Earth Science, 2022)

Ag2Se quantum dots damage the nervous system of nematode Caenorhabditis elegans - Xue Liang; Xinyu Wang; Jin Cheng; Xiaomeng Zhang; Tianshu Wu (Bulletin of Environmental Contamination and Toxicology, 2022)

Temperature Field in Bone During Robotic Dental Implant Drilling: Theoretical Models and In Vitro Experiments - Qi Cui; Russell Wang; Lisa-Marie Faller; Tianshu Kan; Xianfeng Jiang; Fudong Zhu; Weidong Zhu; Yunfeng Liu (Journal of Medical and Biological Engineering, 2022)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

JNK-dependent phosphorylation and nuclear translocation of EGR-1 promotes cardiomyocyte apoptosis - Jinrun Zhou; Yujuan Yao; Jiaojiao Zhang; Zhaohui Wang; Tianshu Zheng; Yao Lu; Weihua Kong; Jing Zhao (Apoptosis, 2022)

Dichloroacetic acid-induced dysfunction in rat hippocampus and the protective effect of curcumin - Wei Wei; Qiuying Dong; Wenbo Jiang; Yue Wang; Yingying Chen; Tianshu Han; Changhao Sun (Metabolic Brain Disease, 2021)

Anatomy and lignin deposition of stone cell in Camellia oleifera shell during the young stage - Qianqian Wang; Jinbo Hu; Tianshu Yang; Shanshan Chang (Protoplasma, 2021)

Bioinformatic analysis of the complete genome sequence of Pectobacterium carotovorum subsp. brasiliense BZA12 and candidate effector screening - Yufei Huang; Changyuan Liu; Hui Wang; Tianshu Guan; Li Liu; Shuyi Yu (Journal of Plant Pathology, 2019)

Observational Study on the Supercooled Fog Droplet Spectrum Distribution and Icing Accumulation Mechanism in Lushan, Southeast China - Tianshu Wang; Shengjie Niu; Jingjing Lü; Yue Zhou (Advances in Atmospheric Sciences, 2019)

Study on Enhanced Dissolution of Azilsartan-Loaded Solid Dispersion, Prepared by Combining Wet Milling and Spray-Drying Technologies - Tianshu Lu; Yinghua Sun; Dawei Ding; Qi Zhang; Rui Fan; Zhonggui He; Jing Wang (AAPS PharmSciTech, 2017)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

The Expression and Significance of the Plasma Let-7 Family in Anti-N-methyl-d-aspartate Receptor Encephalitis - Jing Zhang; Xiaoge Xu; Shaoyun Zhao; Zhe Gong; Peidong Liu; Wenjuan Guan; Xia He; Tianshu Wang; Tao Peng; Junfang Teng; Yanjie Jia (Journal of Molecular Neuroscience, 2015)

Interdecadal change of the northward jump time of the western Pacific subtropical high in association with the Pacific decadal oscillation - Tianshu Ye; Qian Shen; Kuo Wang; Zhisen Zhang; Junhu Zhao (Journal of Meteorological Research, 2015)